The Preconception Period analysis of Risks and Exposures Influencing health and Development (PrePARED) consortium. Issue 6 (28th October 2019) - Harville, Emily W.; Mishra, Gita D.; Yeung, Edwina; Mumford, Sunni L.; Schisterman, Enrique F.; Jukic, Anne Marie; Hatch, Elizabeth E.; Mikkelsen, Ellen M.; Jiang, Hong; Ehrenthal, Deborah B.; Porucznik, Christina A.; Stanford, Joseph B.; et al.
Abstract: Background: Preconception health may have intergenerational influences. We have formed the PrePARED (Preconception Period Analysis of Risks and Exposures influencing health and Development) research consortium to address methodological, conceptual, and generalisability gaps in the literature. Objectives: The consortium will investigate the effects of preconception exposures on four sets of outcomes: (1) fertility and miscarriage; (2) pregnancy‐related conditions; (3) perinatal and child health; and (4) adult health outcomes. Population: A study is eligible if it has data measured for at least one preconception time point, has a minimum of selected core data, and is open to collaboration and data harmonisation. Design: The included studies are a mix of studies following women or couples intending to conceive, general‐health cohorts that cover the reproductive years, and pregnancy/child cohort studies that have been linked with preconception data. The majority of the participating studies are prospective cohorts, but a few are clinical trials or record linkages. Methods: Data analysis will begin with harmonisation of data collected across cohorts. Initial areas of interest include nutrition and obesity; tobacco, marijuana, and other substance use; and cardiovascular risk factors. Preliminary results: Twenty‐three cohorts with data on almost 200 000 women have combined to form this consortium, begun in 2018. Twelve studies are of women or couples actively planning pregnancy, and six are general‐population cohorts that cover the reproductive years; the remainder have some other design. The primary focus for four was cardiovascular health, eight was fertility, one was environmental exposures, three was child health, and the remainder general women's health. Among other cohorts assessed for inclusion, the most common reason for ineligibility was lack of prospectively collected preconception data. Conclusions: The consortium will serve as a resource for research in many subject areas related to preconception health, with implications for science, practice, and policy.